Pemberdayaan Buruh Migran Indonesia (BMI) di Singapura: Penyusunan Panduan Kehidupan Berbangsa dan Bernegara - Pramono, Muhamad Fajar; Saifulloh, Ahmad; Amalia, Novi Rizka; b. Hj. Embek, Mohd Jakfar (Universitas Widya Mataram, 2024)
It is known that the number of BMI in Singapore in 2020 was 88 thousand people, including those from Ponorogo. On the other hand, the population in Singapore consists of various ethnicities and religions. Of course this also has an influence on religious life. The aim of community service with Madani Intitut Singapore is to prepare guidelines for national and state life for BMI in Singapore, especially in worship. The implementation method used in this service is in the form of collaboration with Madani Intitut by carrying out various activities, including: hearings, counseling and hearings. The results of this collaborative service, apart from obtaining an MoU with Madani Intitut Singapore, are also the preparation of practical guidelines for national and state life for Indonesian female workers in Singapore, especially in worship for Indonesian female workers in Singapore. The conclusion from the activity is that Singapore is a country that upholds pluralism, meritocracy and the supremacy of law. The key is that all agreements are stated in the employment agreement, including in worship. Then the state will guarantee the rights of the community, including BSI in Singapore, to worship.